2012
DOI: 10.1016/j.neurobiolaging.2011.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and frontostriatal networks in cognitive aging

Abstract: Recent studies have linked dopamine to differences in behavior and brain activity in normal individuals. We explored these relationships in older and younger adults by investigating how functional connectivity between the striatum and prefrontal cortex is related to caudate dopamine and verbal working memory task performance. We studied 12 young and 18 older participants with functional magnetic resonance imaging (fMRI) during this task, and used positron emission tomography with the tracer 6-[18F]-fluoro-L-m-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 54 publications
6
60
0
2
Order By: Relevance
“…It is therefore biologically plausible that age-related reductions in caudate D1 receptor densities contribute to age-related reductions in functional connectivity of the prefrontal cortex to the right parietal cortex during WM. Further support for this notion comes from a recent study that found a relation between DA and age-related connectivity reductions of right inferior frontal gyrus to caudate during WM (Klostermann et al, 2011). Klostermann et al constrained their fMRI analysis to the caudate, whereas in the present study, we used GRF cluster-size correction, which likely prevented us from detecting connectivity differences of smaller extent such as those with the striatum.…”
Section: Decreased Frontoparietal Connectivity In Aging and Links To mentioning
confidence: 54%
“…It is therefore biologically plausible that age-related reductions in caudate D1 receptor densities contribute to age-related reductions in functional connectivity of the prefrontal cortex to the right parietal cortex during WM. Further support for this notion comes from a recent study that found a relation between DA and age-related connectivity reductions of right inferior frontal gyrus to caudate during WM (Klostermann et al, 2011). Klostermann et al constrained their fMRI analysis to the caudate, whereas in the present study, we used GRF cluster-size correction, which likely prevented us from detecting connectivity differences of smaller extent such as those with the striatum.…”
Section: Decreased Frontoparietal Connectivity In Aging and Links To mentioning
confidence: 54%
“…They also found a strongly connected network involving the rhinal cortex (BA 28,34,35,36) in elderly individuals. In contrast, Klostermann et al (2012) found that functional connectivity in the right caudate correlated with working memory demands, especially for young subjects. We, on the other hand, found a high hubness of the caudate rather for seniors.…”
Section: Age-related Differences In Memory Networkmentioning
confidence: 71%
“…In working memory tasks, older adults who retrieved their memory faster showed greater activity in the dorsal lateral prefrontal cortex (DLPFC) than those who did slower, while the same comparisons in younger adults showed the opposite pattern (Rypma and D'Esposito, 2000). These studies support the premise that aging alters the activation patterns of local brain regions, and that these regions interact to function globally as a network (Klostermann et al, 2012).…”
mentioning
confidence: 66%